The dynamics of structural deformations of immobilized single light-harvesting complexes - Bopp, Martin A. (The National Academy of Sciences, 1999)
Single assemblies of the intact light-harvesting complex LH2 from Rhodopseudomonas acidophila were bound to mica surfaces at 300 K and examined by observing their fluorescence after polarized light excitation. The complexes are generally not cylindrically symmetric. They act like elliptic absorbers, indicating that the high symmetry found in crystals of LH2 is not present when the molecules are immobilized on mica. The ellipticity and the principal axes of the ellipses fluctuate on the time scale of seconds, indicating that there is a mobile structural deformation. The B850 ring of cofactors shows significantly less asymmetry than B800. The photobleaching strongly depends on the presence of oxygen.